Raman Study of CVD Graphene Irradiated by Swift Heavy Ions - E.A. Kolesov; M.S. Tivanov; O.V. Korolik; P. Yu. Apel; V.A. Skuratov; A.M. Saad; I.V. Komissarov; A. Swic; P.V. Żukowski; T.N. Koltunowicz (Журнал нано- та електронної фізики)
CVD-graphene on silicon was irradiated by accelerated heavy ions (Xe, 160 MeV, fluence of 1011 cm 2) and characterized by Raman spectroscopy. The defectiveness of pristine graphene was found to be dominated by grain boundaries while after irradiation it was determined by both grain boundaries and vacancies. Respectively, average inter-defect distance decreased from ~ 24 to ~ 13 nm. Calculations showed that the ion irradiation resulted in a decrease in charge carrier mobility from ~ 4.0 × 103 to ~ 1.3•103 cm2/V s. The results of the present study can be used to control graphene structure, especially vacancies concentration, and charge carrier mobility.